Calcium-independent Phospholipase A(2) (iPLA(2)β)-mediated Ceramide Generation Plays a Key Role in the Cross-talk between the Endoplasmic Reticulum (ER) and Mitochondria during ER Stress-induced Insulin-secreting Cell Apoptosis - Lei, Xiaoyong (American Society for Biochemistry and Molecular Biology, 2008)
Endoplasmic reticulum (ER) stress induces INS-1 cell apoptosis by a pathway involving Ca(2+)-independent phospholipase A(2) (iPLA(2)β)-mediated ceramide generation, but the mechanism by which iPLA(2)β and ceramides contribute to apoptosis is not well understood. We report here that both caspase-12 and caspase-3 are activated in INS-1 cells following induction of ER stress with thapsigargin, but only caspase-3 cleavage is amplified in iPLA(2)β overexpressing INS-1 cells (OE), relative to empty vector-transfected cells, and is suppressed by iPLA(2)β inhibition. ER stress also led to the release of cytochrome c and Smac and, unexpectedly, their accumulation in the cytosol is amplified in OE cells. These findings raise the likelihood that iPLA(2)β participates in ER stress-induced apoptosis by activating the intrinsic apoptotic pathway. Consistent with this possibility, we find that ER stress promotes iPLA(2)β accumulation in the mitochondria, opening of mitochondrial permeability transition pore, and loss in mitochondrial membrane potential (ΔΨ) in INS-1 cells and that these changes are amplified in OE cells. ER stress also led to greater ceramide generation in ER and mitochondria fractions of OE cells. Exposure to ceramide alone induces loss in ΔΨ and apoptosis and these are suppressed by forskolin. ER stress-induced mitochondrial dysfunction and apoptosis are also inhibited by forskolin, as well as by inactivation of iPLA(2)β or NSMase, suggesting that iPLA(2)β-mediated generation of ceramides via sphingomyelin hydrolysis during ER stress affect the mitochondria. In support, inhibition of iPLA(2)β or NSMase prevents cytochrome c release. Collectively, our findings indicate that the iPLA(2)β-ceramide axis plays a critical role in activating the mitochondrial apoptotic pathway in insulin-secreting cells during ER stress.